Association of Serum Uric Acid with Dyslipidemia in Acute Myocardial Infarction patients - Salma, Ummey; Aktar, Parvin; Hasina, Hafsa; Akther, Salma; Islam, Md Hafizul; Sultana, Sheikh Jabin Jakia (Bangladesh Journal of Medical Biochemistry, 2025)
Although the link between hyperuricemia and various diseases like metabolic syndrome, stroke, and coronary artery disease had been recognized, data on the relationship of serum uric acid (SUA) with dyslipidemia in patients with acute myocardial infarction (AMI) are limited. This study was conducted to evaluate the association of serum uric acid with dyslipidemia in patients with acute myocardial infarction (AMI) at Chittagong Medical College Hospital, Chattagram, Bangladesh. This was a hospital based cross-sectional analytical study comprising one hundred AMI patients admitted in coronary care unit (CCU) in Chittagong Medical College Hospital between July 2020 to June 2021. Important variables in this study were serum uric acid, serum fasting total cholesterol, triglycerides, HDL-C, LDL-C, waist circumference, BMI, age and gender. Sixty-two percent AMI patient had hyperuricemia. Increased serum uric acid was significantly associated with increased TG, total cholesterol, LDL level and decreased HDL level in AMI patients. Serum uric acid significantly correlated with components of fasting lipid profiles in AMI patients. The proportion of patients with hyperuricemia was high in AMI patients. Serum uric acid was associated and correlated with components of fasting serum lipid profiles. Bangladesh J Med Biochem 2021; 14(2): 65-72